Transcrestal sinus lift with simultaneous implant placement using osseodensification in posterior maxilla with residual bone height of 4-6 mm - Elsaid, Mohammed Gamal Abdelftah Hamed; Aboelhasan, Mohsen Fawzy; Shuman, Mohammad Abd Elhamied; Alashmawy, Mohammed Mahgob Mohamed; Abdelrahman, Ahmed Omar Ahmed; Elwaseef, Safwat Saber Mohamed Mursey Ali (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the transcrestal sinus lift using Osseodensification techniquewith simultaneous implant placement. Material and Methods: In this case series 7 patients who neededimplant placement in the atrophic posterior maxilla were enrolled. In all the cases the residual bone heightbetween the sinus floor and the alveolar crest was 4-6 mm. Transcrestal sinus lift was performed usingOsseodensification with simultaneous implant placement. Cone-beam computed tomography (CBCT) wereobtained immediately postoperative and 6 months after operation. Implant stability using Osstell® wereassessed at the time of implant placement and implant exposure (6 months). Results: The results showedthat the mean bone height gain was 5.33±0.83mm at 6 months postoperatively. Mean bone density valuewas 818.43±109.63 HU. Mean ISQ value was 80.00±3.11 at 6 months postoperatively. The duration ofsurgical procedure (minutes) ranged between 25-38 minutes with an average of 30.86±4.10 minutes.Conclusion: The crestal maxillary sinus floor elevation using Osseodensification technique with simultaneousimplant placement provide superior results regarding bone density and implant stability and less durationof surgical procedure.KEYWORDSSinus floor augmentation; Bone substitutes; Alveolar bone loss; Osteotomy; Dental implantation; Cone-beamcomputed tomography.